ARENA FUTSAL UPAUJAYA DI KECAMATAN UPAU KABUPATEN TABALONG - Tetno, Handrian Pranata; Hadinata, Irwan Yudha (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Sport is one of the routine activities that a person does to maintain health, Futsal becomes a trend in the pleasure of young people and also in all circles, futsal is also no different from the game of football because both are played by kicking, the difference is that futsal is very easy not to require a large field and a lot of players. Based on the background of the problems raised from this report, namely how to realize the design of a Futsal Arena (Indoor) Type C equivalent that is creative and has a profit in the district of Upau. The method used to solve this problem is the design method is a method of solving problems with programmatic concepts. The design method is the answer to a problem that will encompass the needs in a building. By focusing on space, shape, function, construction.